Influence of Substrate Temperature On Optical Properties of CdO Thin Films (Journal of the College of Basic Education, 2023)
CdO thin films have been prepared utilizing chemical spray pyrolysis technique. Absorbance and transmittance spectra have been recorded in order to study the reflectance, kind of transition ,extinction coefficient refractive index and dielectric Constant in real and imagery parts, all as a function of substrate temperature. It was found that all the investigated parameters affect by Substrate temperature.